2021
DOI: 10.3389/fpsyg.2020.609371
|View full text |Cite
|
Sign up to set email alerts
|

Are Recycling People Also Saving? Costliness Matters

Abstract: In view of the fact that vigorously promoting recycling has become a viable means to promote sustainable development, it is important to better understand the impact of recycling efforts on subsequent resource saving behavior. This research empirically examines the effects of recycling efforts on subsequent resource saving by analyzing the survey data of 356 college students in China. The recycling efforts, environmental self-identity and feeling of pride were measured using existing scales while saving behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Participants were asked to evaluate how often they engaged in the three aspects of recycling in their daily life over the past year on a five-point Likert scale ranging from “never” to “always.” An earlier study showed that these three WM items together with green purchase behavior could be empirically differentiated from reducing energy use, conserving water, and choosing public transportation when going out, and could be regarded as high-cost pro-environmental behavior for university students in China ( Wu and Zhu, 2021 ). Similarly, Wei et al (2021) also differentiated waste reduction such as bringing reusable bags when shopping from electricity and water saving, and identified the former as costly saving behavior for Chinese university students.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to evaluate how often they engaged in the three aspects of recycling in their daily life over the past year on a five-point Likert scale ranging from “never” to “always.” An earlier study showed that these three WM items together with green purchase behavior could be empirically differentiated from reducing energy use, conserving water, and choosing public transportation when going out, and could be regarded as high-cost pro-environmental behavior for university students in China ( Wu and Zhu, 2021 ). Similarly, Wei et al (2021) also differentiated waste reduction such as bringing reusable bags when shopping from electricity and water saving, and identified the former as costly saving behavior for Chinese university students.…”
Section: Methodsmentioning
confidence: 99%
“…However, recycling efforts only measure the degree of individual past recycling behaviour, but it does not capture the costliness of recycling behaviour, nor does it reflect whether individuals voluntarily implement recycling. Therefore, we borrowed the concept of the costliness of recycling from We et al [ 52 ] to reflect the perceived difficulty and cost of individuals involved in recycling behaviour. Typical items included: I spend time on recycling.…”
Section: Methodsmentioning
confidence: 99%
“… I feel good about my recycling efforts. Costliness of recycling (adapted from [ 52 ]) I spend time on recycling. I paid mental efforts for recycling I paid extra money for recycling.…”
Section: Table A1mentioning
confidence: 99%
“…When deeply engaged in positive and socially desirable behaviors-in this context, recycling efforts-consumers feel they have contributed to progressing toward environmental goals, resulting in increased feelings of pride [4]. In their study, Wei et al [64] concluded that consumers' recycling efforts positively influence their feelings of pride. These studies align with a recent trend of research exploring the relationship between sustainable consumption and the feeling of pride in depth [65][66][67].…”
Section: Feelings Of Pridementioning
confidence: 99%